NEW ‘CRIMMIGRATION’ OR THE OLD POLITICAL ECONOMY OF PUNISHMENT? TWO CRIMINOLOGICAL APPROACHES ON THE BORDER CONTROL POLICY IN CHILE - Quinteros, Daniel (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
This article presents the two main theoretical approaches to understand the State’s punitive control over migrant population from a criminological perspective. On the one hand, the ‘crimmigration’ thesis states that we are facing novel assemblages between penal and border control over the past decades, which are two key functions of the State’s sovereignty. On the other, from a critical perspective, the idea of novelty has been disputed since punitive control of migration has been claimed to be another regulatory mechanism of labour market and the economy, thus reviving the classical point of view from the political economy of punishment.In a context where Chile has doubled the size of foreign population during the last decade, results from a recent research on the administrative sanctions imposed due to border control infringements between 2010 and 2014 in four regions of Chile are discussed. Therefore, the present analysis is based on a study that sought to explore and describe the estimated number of sanctions due to border control infringements by type, and its relationship with personal characteristics of the offender and other procedural aspects. For this, a representative sample of administrative acts issued in the regions of Arica y Parinacota, Tarapacá, Antofagasta and Metropolitana is analysed through chi-square test and multiple correspondence analysis.Finally, it is concluded that both crimmigration and the political economy of punishment could be very powerful analytical tools to understand border control policy, especially regarding the significant Latin American presence within Chile.